2017
DOI: 10.3389/fnmol.2017.00164
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Effects of PGC-1alpha Silencing in MPP+ Treated Human SH-SY5Y Neuroblastoma Cells

Abstract: The dopaminergic neuron degeneration and loss that occurs in Parkinson’s disease (PD) has been tightly linked to mitochondrial dysfunction. Although the aged-related cause of the mitochondrial defect observed in PD patients remains unclear, nuclear genes are of potential importance to mitochondrial function. Human peroxisome proliferator-activated receptor γ coactivator-1alpha (PGC-1α) is a multi-functional transcription factor that tightly regulates mitochondrial biogenesis and oxidative capacity. The goal of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 41 publications
3
29
0
Order By: Relevance
“…Totally, studies on changes in PGC1α levels have provided inconsistent data in different PD models. One study showed that PGC1α mRNA was up‐regulated in SH‐SY5Y cells in response to acute MPP + treatment for 24 hours, closely mirroring our result . Torok et al also reported that the PGC1α mRNA levels were increased in the brain of an acute MPTP‐intoxicated mouse model of PD .…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Totally, studies on changes in PGC1α levels have provided inconsistent data in different PD models. One study showed that PGC1α mRNA was up‐regulated in SH‐SY5Y cells in response to acute MPP + treatment for 24 hours, closely mirroring our result . Torok et al also reported that the PGC1α mRNA levels were increased in the brain of an acute MPTP‐intoxicated mouse model of PD .…”
Section: Discussionsupporting
confidence: 88%
“…PGC1α is a master regulator of mammalian mitochondrial biogenesis in response to disparate physiological or pathological stresses and deemed to be a valuable potential therapeutic target for PD. 9,10 PGC1α plays an indispensable role in normal function of mitochondria, and its deficiency can participate in neurodegenerative processes. On top of that, its overexpression was proven to be neuroprotective against neurotoxins in several models.…”
Section: Decreased Expression Of Pgc1α and Tfam Negatively Correlatmentioning
confidence: 99%
See 3 more Smart Citations